Perancangan Sarana Pengangkut Bergerak Menggunakan Hub Motor Menggunakan Pengendali Elektronika - Hari Satriyo Basuki (Pusat Penelitian Informatika - LIPI, 2009)
Transport utility using diesel motor or electrical motor as its movement power is used in many part of life and industries, it will be used for material handling, human transportation, dangerous material handling as well as in automation industries.The component are easy to find in the domestic and regional market and it makes so easy to build the system.In this paper will be discussed about design of a transport utility using hub motor for common purposes. The hub motor normally use for electric cycles, electric scooter, electric motorcycles. In this design will be used 24 Volt DC 24 AH baterai for 8 hours usage, easy and short charging time.Keywords: transporter, controller, hub motor